Neuromuscular control strategies of the trunk antagonist muscles during the Biering-Sorensen test in individuals with recurrent low back pain and healthy subjects - Morita, Ângela Kazue; Marques, Nise Ribeiro; Navega, Marcelo Tavella (Universidade Estadual Paulista, 2016)
AbstractOBJECTIVES To compare the activation pattern of the trunk antagonistic muscles and also the myoelectric manifestations of muscle fatigue between subjects with and without recurrent non-specific low back pain, during the fatigue provocation of the erector spinae.METHODS The study involved 19 subjects with recurrent low back pain with a non-specific cause (seven men, 12 women, 38.53 ± 8.12 years, 68.35 ± 18.12 kg, 1.66 ± 0.09 m), and 19 healthy subjects (seven men, 12 women, 40.42 ± 8.63 years, 69.57 ± 12.76 kg, 1.64 ± 0.07 m). The electromyographic signal of the internal oblique, lumbar multifidus, rectus abdominis and lumbar iliocostalis muscles, bilateral, were collected during Biering-Sorensen test execution.RESULTS The group with low back pain showed a lower co-contraction rate of the internal oblique/lumbar multifidus (p = 0.006) and lower activation amplitude of the internal oblique (p = 0.019), both on the right side when compared to the group without low back pain. No differences were observed between the groups for muscle fatigue indicators (p > 0.05).CONCLUSION When the erector spine muscle fatigue occurs - even when the groups were similar as to the ability of extensors muscles to resist fatigue - differences were found between subjects with and without low back pain regarding the recruitment pattern of the task antagonist muscle, because subjects with low back pain showed lesser activation and co-contraction in relation to the healthy group.
Keywords: muscle fatigue; abdominal muscles; electromyography; muscle contraction